Novel therapeutic interventions for p53-altered tumors through manipulation of its family members, p63 and p73 - Venkatanarayan, Avinashnarayan (Cell Cycle, 2015)
TP53 is highly mutated in human cancers, thus targeting this tumor suppressor pathway is highly desirable and will impact many cancer patients.(1,2) Therapeutic strategies to reactivate the p53-pathway have been challenging,(3,4) and no effective treatment exists.(5) We utilized the p53-family members, p63 and p73, which are not frequently mutated in cancer, to treat p53-defective cancers. The N-terminal splice variants of p63 and p73 are denoted as the TA and ΔN isoforms. We recently demonstrated that deletion of either ΔNp63 or ΔNp73 in p53-deficient mouse tumors results in tumor regression mediated by metabolic programming. Using this strategy, we identified pramlintide, a synthetic analog of amylin, as an effective treatment for p53 deficient and mutant tumors. Here, we show the utility of using pramlintide, as a potential cancer preventive option for p53-deficient tumors in mouse models. Additionally, we found that in vivo inhibition of both ΔNp63 and ΔNp73 in combination accelerates tumor regression and increases survival of p53-deficient mice. We report that inhibition of both ΔNp63 and ΔNp73 in combination results in upregulation of 3 key metabolic regulators, IAPP, GLS2, and TIGAR resulting in an increase in apoptosis and tumor regression in ΔNp63/ΔNp73/p53 deficient thymic lymphomas. These data highlight the value of generating inhibitors that will simultaneously target ΔNp63 and ΔNp73 to treat cancer patients with alterations in p53.